[18F]FDG PET/CT imaging in hyperthyroid myopathy presenting initially as myasthenia: a case report - Dang, Na; Zhao, Yabo; Wang, Jiehuan; Yu, Hao; Liu, Qingxu; Cao, Guanjie; Chen, Yueqin; Du, Min (Frontiers in Medicine, 2026)
BackgroundMuscle weakness can be a clinical manifestation of a wide range of diseases, often with an obscure etiology and a high risk of misdiagnosis. [18F]FDG PET/CT has been widely studied in tumors and inflammatory myopathies; however, reports on [18F]FDG PET/CT imaging of hyperthyroid myopathy are exceedingly rare, particularly in patients with a history of malignancy, in whom the diagnostic process is especially challenging.CaseA 51-year-old woman presented with bilateral lower-limb weakness of more than 1 year’s duration without an obvious precipitating factor. She had undergone surgery and chemotherapy for endometrial carcinoma 2 years earlier. Whole-body [18F]FDG PET/CT demonstrated diffusely increased [18F]FDG uptake in skeletal muscles throughout the body, with a maximum standardized uptake value (SUVmax) of 5.7. Both thyroid lobes were enlarged, with decreased density and diffusely increased [18F]FDG uptake (SUVmax 3.1). Post-treatment changes of endometrial carcinoma were noted, with no evidence of metabolically active tumor recurrence or metastasis. Laboratory tests revealed elevated thyroid hormone levels and a thyroid-stimulating hormone level <0.01 mIU/L. Thyroid ultrasonography showed diffuse enlargement with heterogeneous echotexture and increased vascularity. Electromyography indicated peripheral nerve damage with suspected myogenic involvement. The clinical diagnosis was hyperthyroid myopathy. The patient recovered after treatment with methimazole, leucogen tablets, and propranolol hydrochloride.ConclusionIn patients presenting with muscle weakness, when whole-body [18F]FDG PET/CT shows diffuse hypermetabolism of skeletal muscles mimicking inflammatory myopathy, and concomitant abnormal thyroid metabolism is detected, hyperthyroid myopathy should be considered.